PENGEMBANGAN E-MODULE GEOGEBRA BERBASIS PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMAPUAN SPASIAL MATEMATIS - Pitriyani; , Irena Puji Luritawaty; Tina Sri Sumartini (Tadris Matematika, 2025)
Electronic modules are one of the learning resources by technological developments. This research aims to develop a Problem-Based Learning-based GeoGebra e-module to improve students' low mathematical spatial ability. The type of research used is development research (R&D) with the ADDIE model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The instruments used were spatial ability test sheets, questionnaires, and interviews. Data collection uses spatial ability tests, field notes, and interviews. The development of the e-module was carried out with the Canva application which is integrated with GeoGebra and Youtube on prism space building materials. The validation of the e-module is carried out by the mathematics teacher as the validator of the material expert and the ICT teacher as the validator of the media expert. The e-module trial was conducted on 38 students of one of the junior high schools in Garut Regency in the 2024/2025 school year who were selected using the purposive sampling technique. The results of the study showed that the GeoGebra e-module with a feasible category based on the validity aspect through the test of media experts and material experts with a percentage of 81%, the practical aspect through a student response questionnaire with a percentage of 85% and the teacher's response with a percentage of 83%, and the effectiveness aspect based on the test results as many as 80% of students have met the KKM score. Therefore, the PBL-based GeoGebra e-module is feasible to use and can improve the spatial mathematical ability of junior high school students in spatial building materials.